INVESTIGATING STUDENNTS’ DIFFICULTIES IN SPEAKING ENCOUNTERED BY THIRD STUDENTS OF UNISMA - Hamimah Istiqomah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: The aim of this study is to investigate students’ difficulties, cause of difficulties, students’ strategies, and students’ perception in speaking learning. The data was gained by qualitative method using digital documentation and deep interview. The participant of this research are third semester of English Department of University of Islam Malang. Coring rubric and interviewed used to collect the data. Scoring rubric used English that was adopted from (Brown & Abeywickrama, 2010). The language of open ended interview used was mix between English and Indonesia was conducted online. The data was analyzed using (Creswell, 2013). From the data identification, Students found difficulties in speaking were on fluency, grammar mastery, and topic discussion. Furthermore, some factors influencing the difficulties found, there were lack of self-confidence, getting feedback, and memorization. Fortunately, there were five strategies used by the students to overcome their difficulty by gaining more input from listening and reading extensively, looking for interesting topic, practicing speaking, and making a small note. Also, it was found about students’ perception on steps done in making video could improve their speaking skill by seeing the process in making video, as well as Instagram as the platform used in posted the video assignment considered the students to perform better and seek to upload their best video assignment.Key words: Difficulties in Speaking English, Causes in speaking difficulties